Does gender matter in effective management of plant disease epidemics? Insights from a survey among rural banana farming households in Uganda - Bailey, Arwen (Bioversity International, 2017)
Presented by Arwen Bailey (Bioversity International), as part of the Annual Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research, Amsterdam, 5-6 December 2017.)